THE POLITICS OF THE COMMONS IN POST-NEW ORDER BALI - Pramana, Gede Indra (Universitas Padjadjaran, 2024)
This research describes the governance practices of the commons in Bali, including land, water sources, coastal areas, and forests, which are communally owned and managed. The relationship between the state and the community has led to changes in this governance. The author examines the practice of governing the commons in the context of post-New Order Bali, offering an alternative to dominant governance that often overlooks the common welfare. This is a qualitative study that utilizes a case study method to explore alternative governance of the commons in Bali. The study examines the governance of the commons in Tenganan Pegringsingan and the Masyarakat Adat Dalem Tamblingan, and finds that community groups (Sekaa) are directly involved in the management of the commons. Furthermore, it appears that government intervention in village affairs has had detrimental impact.